A ouvidoria pública da Universidade Federal do Tocantins como instrumento de aplicação das formas de resolução consensual de conflitos entre professor-aluno - Rodrigues, Jacqueline Araújo (Universidade Federal do Tocantins, 2020)
The present propositional study deals on the instrument of the public ombudsman’s Office of the Federal University of Tocantins in the treatment of interpersonal conflicts through peaceful solutions in the professor/student relationship in the context of the Federal University of Tocantins. The main aim of this study was to analyze how the actions of the ombudsman might contribute to the implementation of the education right through a new arrangement and institutional instrument aiming to resolve the interpersonal conflicts in academic relationships, with a focus on the pedagogical context. The present research aimed to present a proposal for the establishment and standardization draft of a consensual conflict treatment chamber, connected to the public ombudsman’s Office of the Federal University of Tocantins. The chamber should be operated by the general ombudsman, which might attend to all the academic community, but with a particular focus on the treatment of the questions related to students and teachers, which represent the most affected areas by the conflicts, as the investigation will display. The research was performed with a qualitative and quantitative approach, by the document analysis of the statements data of the citizens in the public ombudsman’s Office of the UFT from 2015 to 2018. The analysis focused on the statements presenting an antagonism between professors and students. The pieces of information of the 2015-2018 annual reports of the ombudsman supported the data gathering. The study also analyzed the data from the official websites of the Federal University of Tocantins and the platform “Resolveu?”of the Federal Government. To substantiate our research, we performed a comprehensive study of the institution of the public ombudsman’s Offices, identifying its birth historically, and exploring in-depth the public ombudsman’s Offices inside the public institutions of higher education in Brazil. Through the analysis of the adequate media for theresolution of conflicts, we can define the definition of the use in case of divergence in the mediation and conciliation, as suggested by the new Public Service User defense Code, basing on the definition and study or the interpersonal conflict and its consequences.